A randomized, double-blind, placebo-, and positive-controlled clinical pilot study to evaluate the efficacy and tolerability of standardized aqueous extracts of Terminalia chebula and Terminalia bellerica in subjects with hyperuricemia - Usharani P; Nutalapati C; Pokuri VK; Kumar CU; Taduri G (Dove Medical Press, 2016)
Pingali Usharani,1 Chandrasekhar Nutalapati,1 Venkata Kishan Pokuri,1 Chiranjeevi Uday Kumar,1 Gangadhar Taduri,21Department of Clinical Pharmacology and Therapeutics, 2Department of Nephrology, Nizam's Institute of Medical Sciences, Panjagutta, Hyderabad, India Objectives: To evaluate the efficacy and tolerability of standardized aqueous extracts of Terminalia chebula and Terminalia bellerica versus febuxostat and placebo on reduction in serum uric acid levels in subjects with hyperuricemia. Materials and methods: A total of 110 eligible subjects with hyperuricemia were enrolled and randomized to either of the five treatment groups – T. chebula 500 mg twice a day (BID), T. bellerica 250 mg BID, T. bellerica 500 mg BID, placebo BID, and febuxostat 40 mg once daily plus an identical placebo – for a duration of 24 weeks. Serum uric acid levels were measured at baseline and at the end of 4, 8, 12, 16, 20, and 24 weeks. Statistical analysis was done using GraphPad Prism Software 4. Results and interpretation: All active treatment groups showed a reduction in serum uric acid levels compared to baseline and placebo. Significant reduction in mean serum uric acid levels started as early as 4 weeks following treatment, compared to baseline, with T. bellerica (500 and 250 mg), febuxostat (P<0.001), and T. chebula 500 mg (P<0.01); an increase in serum uric acid levels was seen with placebo (P<0.05). The serum uric acid levels became steady after 16 weeks of treatment and remained the same until the end of 24 weeks. The reduction of serum uric acid levels in the T. bellerica 500 mg group was nearly twice that of the T. chebula 500 mg group as well as T. bellerica 250 mg group at all time points. T. bellerica 500 mg reduced serum uric acid levels from 8.07±0.87 to 5.78±0.25 compared to febuxostat, which reduced serum uric acid levels from 8.53±0.97 to 4.28±0.67 (P<0.001) at the end of 24 weeks. The efficacy of T. bellerica appeared to be dose dependent. All the formulations were well tolerated. Conclusion: T. bellerica has the potential for treating hyperuricemia as it was devoid of any serious adverse effects in the present study. Further studies are needed to confirm this potential. Keywords: hyperuricemia, febuxostat, Terminalia chebula, Terminalia bellerica